The Effect of Learning Using the LKPD-Assisted PjBL Model on Creative Thinking Ability in Class X Phase E of SMAN 2 Sijunjung - Bunga Amanda Idha; Rio Anshari; Yenni Darvina; Selma Riyasni (Department of Physics Universitas Negeri Padang, 2026)
Students’ creative thinking skills in physics learning, particularly on alternative energy topics, remain relatively low due to teacher-centered instructional practices. This study aimed to examine the effect of the Project Based Learning (PjBL) model assisted by Student Worksheets (LKPD) on students’ creative thinking skills. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes of grade X Phase E students at SMAN 2 Sijunjung, with class X E8 as the experimental group and X E7 as the control group. Data were collected using a creative thinking skills test administered as pretest and posttest. The data were analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed that the experimental class achieved a higher mean posttest score 76.1 compared to the control class 63.1. The t-test results indicated a significant difference at the 5% significance level. These findings indicate that the LKPD-assisted PjBL model has a significant positive effect on students’ creative thinking skills in learning alternative energy concepts.